2020
DOI: 10.1111/vcp.12917
|View full text |Cite
|
Sign up to set email alerts
|

Impact of blood storage duration on hematologic, blood gas, biochemical, and oxidative stress variables in sheep undergoing allogeneic blood transfusions

Abstract: BackgroundHemotherapy in ruminants is limited to whole blood transfusions, sometimes with stored blood for up to 42 days, but little attention has been given to the effect of blood storage times and recipient responses after transfusions.ObjectivesWe aimed to evaluate the hematologic and serum biochemical effects after allogeneic blood transfusion with either fresh or stored blood in sheep. We also sought to examine hematologic and biochemical analyte changes in the store blood.MethodsEighteen sheep underwent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Acute blood loss in this study caused oxidative stress; however, a recent report showed that sheep submitted to acute hemorrhage had reduced GSH values 24 h after blood loss and that transfusion of fresh or stored whole blood promoted the restoration of oxygen supply, and consequent return of initial GSH values [ 15 ]. Blood loss can occur due to different factors and different intensities.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Acute blood loss in this study caused oxidative stress; however, a recent report showed that sheep submitted to acute hemorrhage had reduced GSH values 24 h after blood loss and that transfusion of fresh or stored whole blood promoted the restoration of oxygen supply, and consequent return of initial GSH values [ 15 ]. Blood loss can occur due to different factors and different intensities.…”
Section: Discussionmentioning
confidence: 99%
“…After 24 h of anemia induction, considering the best standards of animal welfare, all sheep were treated and received a transfusion of whole blood and were followed until full recovery, as described by Sousa et al [ 15 ], who used the same animals from this study. A minimum number of sheep was used in this study since animals were divided in three groups of six sheep, following the study of Sousa et al [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The blood storage bags used in veterinary medicine were developed for the storage of human blood, however studies have been evaluating the viability of such blood bags for the storage of blood of different animal species [7,8]. The CPDA-1 bags contain a solution of citrate, phosphate, dextrose, and adenine (63 mL) that allows the storage of human blood for 35 days, while the CPD/SAG-M bags, in addition to citrate, phosphate, and dextrose (63 mL) have an additive solution in a satellite bag containing saline, adenine, and mannitol (100 mL) that provides a greater supply of energy and phosphate for the survival of red blood cells.…”
Section: Introductionmentioning
confidence: 99%